Diazepam affects both level and amplitude of rat locomotor activity rhythm but has no effect on core body temperature - Djeridane, Yasmina; Lemmer, Björn; Touitou, Yvan (Chronobiology international, 2005)
The present study investigates the effects of a chronic administration of diazepam, a benzodiazepine widely used as an anxiolytic, on locomotor activity and body core temperature rhythms in male Wistar rats housed under 12∶12 light∶dark (LD) cycle conditions. Diazepam was administered subcutaneously for 3 wks in a dosage of 3 mg/kg body weight/day, 1 h before the onset of darkness. Diazepam increased the level of locomotor activity from the first day until the end of treatment, and also increased the amplitude of the activity circadian rhythm, but only on the third wk of treatment. Diazepam exerted no effects on the length of the period and did not affect the phase of the locomotor activity rhythm. The body temperature rhythm of rats was affected neither by short‐term (a single injection) nor by long‐term (every day for 3 wks) diazepam treatment. Diazepam lacked effect on body core temperature even on the first day of administration, thereby ruling out the possibility of drug tolerance development. The fact that diazepam affects locomotor activity, but not core body temperature, suggests that different mechanisms mediate the actions of diazepam on locomotor activity and on core body temperature.